Caracterización in vivo de la bioimpedancia del cerebro del pez cebra adulto en los estadios de normoxia, hipoxia e hipoxia severa (2016)
The adult zebrafish is being established as an ideal animal model for neurophysiology studies. As a therapy, neurostimulation is based on the chemical or electrical stimulation of the brain nuclei which can generate variations in the production of neurotransmitters. The electrical stimulus is given by parameters as the bioimpedance that determines the current reaching the tissue. By using the adult zebrafish as an animal model and innovative techniques, the object of the present study is to characterize the bioimpedance of the adult zebrafish brain in conditions of normoxia, hypoxia and severe hypoxia forward to fill an empty gap in the literature about adult zebrafish brain's bio-impedance and open the possibility for studying the action mechanism of the neurostimulation therapy in this animal model.